Effect of various factors on the formation of aminoreductone during the maillard reaction - Trang, Vu Thu; Lam Xuan Thanh (Vietnam Journal of Science and Technology, 2018)
To create a basis for the production of aminoreductone (AR) followed by the use of it as a functional ingredient in food supplements, the effects of heating temperature, heating time, buffer concentration and reducing sugar/amino compound ratio on the formation of aminoreductone (AR), a product formed during the initial stage of the Maillard reaction,were investigated. In the model solution of lactose (262 mM) and butylamine (1.16 M) in 1.28 M phosphate buffer (pH 7.0), AR formation increased during the prolongation of the heating time at heating temperature less than 100oC. In the heated model solution at 100 oC, the maximum amount of AR was obtained as soon after 10 min of heating time. After that, the decreases of the AR formation was observed by the progress of the advanced reactions of AR. The rates of AR formation increased with the increasing phosphate buffer concentration. Moreover, the increasing in AR formation incorporated in the increase of the butylamine/lactose ratio from 0.1 to 5. Our results might give more insight in the discovery of Maillard reactions in food because it suggested tendency of the AR formation and to control the formation of AR during food processing and model system base on the control of initial constituents and reaction conditions.